‘Catching glimpses of disciplinary understanding’: Collaborative teaching, learning, and inquiry (A review of Teaching, Learning, and the Holocaust: An Integrative Approach) (Teaching and Learning Inquiry, 2014)
A review of Teaching, Learning, and the Holocaust: An Integrative Approach.